Case Report: Stüve–Wiedemann syndrome—a rare cause of persistent pulmonary hypertension of the newborn - Jin, Jessica; Rothämel, Paula; Büchel, Johanna; Kammer, Birgit; Brunet, Theresa; Pattathu, Joseph; Flemmer, Andreas W.; Nussbaum, Claudia; Schroepf, Sebastian (Frontiers in Pediatrics, 2024)
Introduction: Persistent pulmonary hypertension of the newborn (PPHN) is alife-threatening condition characterized by hypoxemia due to elevated pulmonary vascular resistance. PPHN commonly arises secondary to various underlying conditions including infection, meconium aspiration and respiratory distress syndrome. Management includes pulmonary vasodilators, mechanical ventilation, oxygen supplementation, vasopressors and volume replacement. Stüve-Wiedemann syndrome (SWS),a rare genetic disorder characterized by bone dysplasia, respiratory distress, hyperthermia and swallowing difficulties, may present with pulmonary hypertension, indicating a poor prognosis. Case description: A term female neonate presented with secondary respiratory failure and severe PPHN of unknown etiology on the 2 nd day of life necessitating intubation. Clinical findings included facial dysmorphia, camptodactyly, skeletal anomalies and generalized muscular hypotonia. Highfrequency oscillation ventilation and surfactant administration yielded marginal improvement. On the 3 rd day of life a severe pulmonary hypertensive crisis necessitated inhaled and systemic pulmonary vasodilators along with volume and catecholamine therapy. Whole exome sequencing revealed a homozygous mutation in the LIFR (Leukemia Inhibitory Factor Receptor) gene, consistent with Stüve-Wiedemann syndrome. Discussion/Conclusion: The case underscores the importance of considering and prompting evaluation of rare genetic causes in the differential diagnosis of PPHN, especially when other abnormalities are present, and conventional therapies prove inadequate. Therapeutic strategies must account for the different pathophysiology of primary PPHN including vascular remodeling as seen in SWS, which may not respond to pulmonary vasodilators typically employed in secondary PPHN due to vasoconstriction. In this case, the patient responded well to treatment for primary PPHN, but the use of high-frequency oscillation ventilation and surfactant was not helpful.